Improving The Students’ Vocabulary Achievement by Using Guessing Games Technique - Siregar, Horia; Mariana, Mariana; Purwana, Rudi; Afrida, Shanti (International Journal of Cultural and Social Science, 2023)
Learning vocabulary of foreign languages is very important. To develop the student's language skills in reading, listening, speaking and writing, the learners must master vocabulary. The mastery of vocabulary is needed by each language skill. This study is aimed at improving students' vocabulary achievement through guessing word games. The research of this study was conducted using classroom action research. The subject of this study was the eight grade students' of MTs Tarbiyah Islamiyah Hamparan Perak consisting of 33 students. To collect the data, the instruments used were quantitative data (vocabulary test) and qualitative data (diary notes, interviews, photographs, and observation sheets). In analyzing the data, the mean of the students' score for the pretest was (52.42), for test I was (58.18), and the mean of the students' score for the test II was (72.12). Based on diary notes, interviews, photos and observation sheets, it showed that the expression and excitement of the students were also improved. It was concluded that teaching vocabulary through guessing word games could improve students' vocabulary achievement